Growth-Promoting Bacteria, Silicon Supply and Nitrogen Fertilization in Zoysia Grass Production Area - Almeida Moreira Girardi, Vitória [UNESP]; da Silva Oliveira, Carlos Eduardo [UNESP]; de Lima, Bruno Horschut [UNESP]; Gato, Isabela Martins Bueno [UNESP]; Ferreira dos Santos, Patrick Luan [UNESP]; Boleta, Guilherme Henrique Marcandalli [UNESP]; Rezende, Brian Turati [UNESP]; Jalal, Arshad [UNESP]; Filho, Marcelo Carvalho Minhoto Teixeira [UNESP] (Taylor & Francis, 2025)
One of the alternatives for reducing nitrogen fertilization is the use of plant growth-promoting bacteria (PGPB), such as Pseudomonas fluorescens and Azospirillum brasilense, which can provide a sustainable form of production, with increased profitability for rural producers, because bacteria are a low-cost technology compared to fertilizer. In view of the above, the objective of this study was to evaluate the effect of inoculation with plant growth-promoting bacteria (P. fluorescens and A. brasilense) combined with the supply or not of Si and doses of nitrogen (N) in zoysia grass sod production area. The experimental design was in randomized blocks with 12 treatments arranged in a 3 × 2 × 2 factorial scheme, with four replications, in plots of 9 m2. The treatments were: two inoculations with PGPB (A. brasilense and P. fluorescens) and non-inoculated, combined with two doses of N, with or without supply of Si through fertilization (through the commercial fertilizer known as Potasil). There was an increase in the shoot dry matter with the supply of Si, the standard dose of N and the inoculation with PGPB. The standard dose of N promoted an increase in the content of nitrogen (N), phosphorus (P) and potassium (K) in the shoot of Zoysia japonica. There was an effect of inoculation with plant growth-promoting bacteria combined with the supply of silicon and N rates in the zoysia grass production area, where the use of Pseudomonas combined with the application of Si with 75% of the N dose is recommended.
Keywords: Azospirillum brasilense; nitrogen supply; potassium silicate; Pseudomonas fluorescens; Zoysia japonica